2020
DOI: 10.22329/csw.v21i2.6459
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Latino Fathers’ Perceptions of Child Abuse and Neglect

Abstract: The objective of this qualitative research was to study the lived experiences of child abuse and neglect for immigrant Latino fathers whose children are involved in the child protection process. We documented the narratives of nine immigrant Latino fathers attending fatherhood groups regarding their perceptions of child abuse and neglect.The immigrant Latino fathers highlighted their lack of agency and marginalization due to acculturative parenting stress, structural discrimination, and immigration status. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…FFN provider support groups were also consistently acknowledged as a resource for this sample. Past qualitative studies often cite parent support groups as a valuable resource for Latinx immigrant families as they provide trustworthy and safe spaces for parents to discuss their experiences and facilitate acculturation by expanding their support networks (Ayón, 2014;Kohli & Fineran, 2020). Even if they may not always be the parents of these children, Latinx immigrant FFN providers -with their close connections and strong commitments to the children -benefit from such peer support groups as well.…”
Section: Discussionmentioning
confidence: 99%
“…FFN provider support groups were also consistently acknowledged as a resource for this sample. Past qualitative studies often cite parent support groups as a valuable resource for Latinx immigrant families as they provide trustworthy and safe spaces for parents to discuss their experiences and facilitate acculturation by expanding their support networks (Ayón, 2014;Kohli & Fineran, 2020). Even if they may not always be the parents of these children, Latinx immigrant FFN providers -with their close connections and strong commitments to the children -benefit from such peer support groups as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study with Latinoimmigrant fathers, participants reported that they lived with a sense of deep conflict about childrearing. Although they reported the benefits of positive parenting and the moral imperative inherent in their dominant culture to raise children without abuse or neglect, they felt marginalized and less able to parent in a desired way due to acculturative parenting stress and reduced agency in their community (Kohli & Fineran, 2020).…”
mentioning
confidence: 99%